Локальный территориально-хозяйственный комплекс (Китей и его округа в IV–VI вв.) - Болгов, Н. Н. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryN. Bolgov. Local Territorial and Economic Complex of Late Bosporus (Cytaion and Its Region in IV-VI Centuries).This article is the first research of the less-researched periods of Bosporian history from the end of the III century to the first half of the VI century AD. Local territorial and economic complex around Cytaion is the main object of this work. This complex was an elementary part of the Late Bosporian political structure too. Natural geographical objects served as borders of this region: lines of hills, sea coasts and the coast of the Churubash Gulf. Cytaion was a center of the Southeast part of European Bosporus. Its archaeological material represents a typical Late Antiquity town. It was a separate political organism that was ruled by its local self-government body. The life of Bosporian aristocracy, especially of the family of Savagus and Faisparta, can be considered as an important factor of the Cytaion'a history.